City, Informality and Poverty: The Polarization of the Street Vendors in Dhaka City, Bangladesh - Hussain, Rasel (Italian Sociological Review, 2019)
The neoliberal society is witnessing a radically unequal and explosively unstable urban world where urbanization is hardly connected with industrialization. The present society portrays a vast humanity warehoused in shantytowns and that is also exiled from the formal world economy but the victory of informality where the process of capital accumulation is dispossession. ‘Dhaka’ the capital of Bangladesh is regarded as the highest densely populated city of the world with 47,400 people living in sq km thus became the focus of my study area as thousands of people are involved and involving in the informal economy. In this research paper, the area of interest falls on ‘Street vending’, the most common urban informal sector of the city. Literature reviewed from global, Asian and regional perspectives to have a greater view about informality with solid theoretical framework of Davis, Castells, Sassen, Harvey, Humphrey, Bayat and Soto. After the engagement of the street vending activities they face series of problems such as harassment, eviction, confiscation and sometimes forced to provide goods in undervalued prices and so on. The State mechanism in most of the cases is responsible to create all of these problems and in this regard police and municipal authority play the key role. Without finding any other sources of subsistence as well as their livelihood they are going through the process of vulnerabilities and sometimes with negotiation. This is the politics of informality. Being the right claim citizen, their rights are constantly violated by the state and associates which make them urban marginal group. Without starting the rehabilitation project for these large segment people it’s not possible to stop informality. It’s the duty of the government to fulfill their demand and include them in the main stream of the society to save them from marginal condition of living.